Optimization of Process Loading Clinker to MV. Star Royal by PT. Varia Usaha Bahari at Maspion Port Gresik - Wibisono, Muhammad Gunawan; Sudirman, Sudirman; Purwiyanto, Didik (Universitas Hang Tuah, 2024)
The main focus of this research is to find out the process of loading clinker onto the MV. Star Royal that the activity is running optimally. The factors include in this research loading and unloading equipment, facilities and infrastructure, human resources, weather conditions. This research will identify each of these factors and analyze their impact on the overall clinker loading process. The research method used in the study is a qualitative method involving direct observation in the field, interviews with relevant parties at PT Varia Usaha Bahari, and analysis of data related to the clinker loading process. With a comprehensive approach, this research aims to provide concrete and implementable recommendations to improve the optimization of the clinker loading process at Maspion Gresik Port. The results of this research are expected to make a positive contribution in improving the performance of PT Varia Usaha Bahari in carrying out clinker loading activities on other vessels. With a deeper understanding of the factors that influence the clinker loading process, it is expected that the company can implement a more optimized strategy in the clinker loading process to better achieve their goals in the future.